2019
DOI: 10.1097/md.0000000000016624
|View full text |Cite
|
Sign up to set email alerts
|

Decreased expression of SLC16A12 mRNA predicts poor prognosis of patients with clear cell renal cell carcinoma

Abstract: Solute carrier family 16, member 12 (SLC16A12) is a highly -expressed protein in the kidney and has been reported to participate in the transport of creatine. However, the clinical values of SLC16A12 in clear cell renal cell carcinoma (ccRCC) have not been explored. SLC16A12 RNA-seq data and clinical information were downloaded from the Cancer Genome Atlas (TCGA) database. We compared its expression in ccRCC and paracancerous tissues, then the result was further validated with our cohort. The impact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…SLC16A12 is a member of the SLC16A family, and its function is not known. A recent study showed that SLC16A12 can be a prognostic factor for patients in KIRC, indicating that SLC16A12 might be a critical tumor suppressor (Mei et al 2019 ). ZIC2 is a member of the ZIC family and is a transcription factor (Inaguma et al 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…SLC16A12 is a member of the SLC16A family, and its function is not known. A recent study showed that SLC16A12 can be a prognostic factor for patients in KIRC, indicating that SLC16A12 might be a critical tumor suppressor (Mei et al 2019 ). ZIC2 is a member of the ZIC family and is a transcription factor (Inaguma et al 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, studies have shown that SLC16A7 is associated with the stem cell characteristics of tumors [ 49 ]. Mei et al found that the expression of SLC16A12 was decreased in renal clear cell carcinoma and was associated with poor prognosis, which has a good prognostic guiding significance [ 50 ]. However, studies on SLC16A4, SLC16A10, SLC16A11, SLC16A13, and SLC16A14 in cancer are still lacking.…”
Section: Discussionmentioning
confidence: 99%
“…The staining intensity was scored from 0 to 3, namely, 0: negative, 1: low, 2: moderate, and 3: high. Semi-quantitative analysis of the IHC staining was performed based on the percentage of positively stained cells and staining density by two pathologists and this analysis method has been previously applied [ 11 ]. Immunostained sections were snapshot using a microscope (Olympus Corporation).…”
Section: Methodsmentioning
confidence: 99%